2013
DOI: 10.5812/jjm.7365
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Load in Seropositive Liver and Kidney Transplant Recipients by Quantitative Real-Time PCR Before and After Transplantation

Abstract: Background: Hepatitis C virus (HCV) infection is one the major health concern among the infected transplant patients. Considering several complications of the disease in them, pre and post-transplantation studies should be performed for monitoring of the infection, as well as, developing new treatment protocols. Objectives: The current study was conducted to determine the Hepatitis C Virus RNA level among seropositive liver and kidney transplant recipients in Namazi Hospital; the main transplantation center in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…As we see, the benefit of SVR for CHC patients was apparent, which would reduce the risk of all-cause mortality and HCC. Even, some studies indicated that SVR would reduce the risk of relapse in HCV infected transplant patients ( 32 ). However, patients achieved SVR still need long-time follow-up, especially some who already had advanced fibrosis before treatment, because of HCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…As we see, the benefit of SVR for CHC patients was apparent, which would reduce the risk of all-cause mortality and HCC. Even, some studies indicated that SVR would reduce the risk of relapse in HCV infected transplant patients ( 32 ). However, patients achieved SVR still need long-time follow-up, especially some who already had advanced fibrosis before treatment, because of HCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies report the controversial effects of the infection before and after transplantation. Recurrence of the disease is asserted in the liver transplant patients who were viremic before the operation ( 3 ), which may develop to cirrhosis in at least 25% of them within 5 years of transplantation ( 4 ). Previous studies indicated that HCV infection can cause liver failure among chronic renal failure (CRF) patients within a long time after kidney transplantation ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method cannot detect whole viral particles but can measure relatively low copy number of viral genomes. Therefore, real-time PCR is more sensitive in comparison to other methods for the measurement of viral loads ( 24 - 26 ).…”
Section: Discussionmentioning
confidence: 99%